2003
DOI: 10.1364/josab.20.002215
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz beam propagation measured through three-dimensional amplitude profile determination

Abstract: To determine the spatio-temporal field distribution of freely propagating terahertz bandwidth pulses, we measure the time-resolved electric field in two spatial dimensions with high resolution. The measured, phasecoherent electric-field distributions are compared with an analytic model in which the radiation from a dipole antenna near a dielectric interface is coupled to free space through a spherical lens. The field external to the lens is limited by reflection at the lens-air dielectric interface, which is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…Different lens shapes (collimating, hemispherical and hyperhemispherical shapes) have been thoroughly characterized by Rudd and Mittleman [138]. Reiten et al performed careful measurements and simulations of the propagation of THz beams through hyperhemispherical lenses and the subsequent optical system of a THz-TDS setup [139,140]. They showed that the THz beam profile emerging from a lens-coupled photoconductive emitter is accurately described by a superposition of Laguerre-Gauss modes, and also discussed the influence of spherical aberration and surface waves on the propagation.…”
Section: Static Terahertz Time-domain Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Different lens shapes (collimating, hemispherical and hyperhemispherical shapes) have been thoroughly characterized by Rudd and Mittleman [138]. Reiten et al performed careful measurements and simulations of the propagation of THz beams through hyperhemispherical lenses and the subsequent optical system of a THz-TDS setup [139,140]. They showed that the THz beam profile emerging from a lens-coupled photoconductive emitter is accurately described by a superposition of Laguerre-Gauss modes, and also discussed the influence of spherical aberration and surface waves on the propagation.…”
Section: Static Terahertz Time-domain Spectroscopymentioning
confidence: 99%
“…12 where the ATR prism has been loaded with distilled water. Figure 12a shows 139 index of refraction p is r = n 1 q 1 (n 1 =n 2 ) 2 sin 2 θ n 2 cos θ n 1 q 1 (n 1 =n 2 ) 2 sin 2 θ +n 2 cos θ : (38) This equation has the solutionŝ…”
Section: Attenuated Total Reflection (Atr) Thz-tdsmentioning
confidence: 99%
“…Because of the inversion symmetry of the resulting 2040 m 2040 m, 4-array centered on ÿ22:5; ÿ15 , the original overlap calculation also applies to the 4-array. The effective array size is considered to be determined by the spatial extent (at the array) of the planar phase coherence of the THz beam, due to the residual phase variation and curvature [36]. The 2 mm 2 mm, 4-array is comparable in size to the spatial phase variations of an incoming 6 mm, 1=e diameter.…”
Section: Volume 93 Number 19 P H Y S I C a L R E V I E W L E T T E Rmentioning
confidence: 99%
“…However, recent measurements show that our THz beams are not Gaussian. 11 If a Gaussian beam were assumed, the absorption would be reduced by only 0.03 cm Ϫ1 at 2 THz. Second, we expect some loss as the structure likely has gaps of several microns between the plates and the mirror edges allowing leakage of the guided mode, although significant efforts were made to reduce this effect.…”
Section: ͑2͒mentioning
confidence: 99%